Utilization of Biogas Energy for Pasteurization in Sembalun Mushroom Initiative - Zubaidah, Teti; Rosmaliati; Rokhmat, Joni; Muntari; Niseng, Zakee; Nurcahaya; Saputra, Ramdani; Akbar, Lalu Muhamad Roviq; Gunada, I Wayan; Hidayat, X Zardht Alex (Pascasarjana Universitas Mataram, 2025)
The Sembalun Mushroom Initiative aims to strengthen food security and resilience to disasters in Sembalun Bumbung and circumstance villages through the utilization of biogas energy for the pasteurization process of mushrooms. These areas are prone to disasters, making the supply of food and sustainable energy a major challenge. The project utilizes cow dung waste as an environmentally friendly biogas source to support pasteurization and mushroom cultivation. Traditionally, mushroom pasteurization processes still use firewood, which triggers deforestation, high carbon emissions, and health risks from smoke. The community service team from the University of Mataram has developed biogas technology as an alternative solution. The biogas installation at the At-Tazkiyah Islamic Boarding School was completed in May 2024 and began operating in July 2024, thereafter a mushroom house has been built for mushroom cultivation in early 2025. During this community service project, a gas pasteurization system is installed and used for pasteurization, followed by training and capacity building for the community in utilizing green energy sources. The aim is to introduce a transition to environmentally friendly technologies, as well as to support innovation, sustainability, and community engagement. The activities are an international collaboration between the Postgraduate Program and the Faculty of Engineering at University of Mataram and the Fatoni University in Thailand. It is expected to expand Unram's international exposure and strengthen cooperation between countries.